Analisis Keterampilan Generik Sains dan Pemahaman Konsep Siswa pada Pembelajaran MASTER - Nugroho Prasetya Adi; Makrifatul Khasanah; Sri Jumini (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2023)
Physics learning is the process of students mastering mathematical concepts in life that are solved through complicated formulas. The research aims to determine the effect and increase in students' conceptual understanding and science generic skills in physics lessons. This research belongs to the experimental research type with a quasi-experimental design using the One Group Pretest-Posttest Design. Sample selection used Nonprobability sampling (total or saturated sample) consisting of 18 eighth-grade students. Data collection techniques used tests and observations. The statistical test results show that tcount < ttable indicates the influence of using the learning model. The study concludes that the use of the MASTER (Motivating, Acquiring, Searching, Triggering, Exhibiting, and Reflecting) learning model with discussion methods can improve students' conceptual understanding and science generic skills in physics. The application of the MASTER learning model is able to improve students' conceptual understanding and science generic skills as seen from the test results before and after treatment, with the post-treatment test results being higher than the pre-treatment test results. The research results show the N-Gain test results for the conceptual understanding variable at 0.18 and for the science generic skills variable at 0.7.